2009
DOI: 10.1542/peds.2008-2780f
|View full text |Cite
|
Sign up to set email alerts
|

Consistently Inconsistent: A Snapshot of Across- and Within-State Disparities in the Prevalence of Childhood Overweight and Obesity

Abstract: BACKGROUND. The epidemic of childhood overweight and obesity is characterized by known disparities. Less is known about how these disparities vary across and within the state in which a child lives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
23
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 25 publications
2
23
0
Order By: Relevance
“…Since Wennberg's seminal paper in 1973, 2 research has demonstrated regional variation (including within- and across-state) for numerous health conditions and medical treatments. In pediatrics, these are as diverse as obesity, 3-5 adolescent pregnancy, 6 emergency department use, 7 hospitalizations, 8 appendicitis rupture, 9 and medical home access 10 or underinsurance 11 for children with special health care needs. Particular attention has been paid to differences seen in urban versus rural locales; the Agency for Healthcare Research and Quality (AHRQ) National Healthcare Disparities Report considers residents of rural areas to be a “priority population.” 12 They are more likely than urban residents to be in fair or poor physical health, 13 and less likely to have seen a health care provider or to have received preventive services.…”
mentioning
confidence: 99%
“…Since Wennberg's seminal paper in 1973, 2 research has demonstrated regional variation (including within- and across-state) for numerous health conditions and medical treatments. In pediatrics, these are as diverse as obesity, 3-5 adolescent pregnancy, 6 emergency department use, 7 hospitalizations, 8 appendicitis rupture, 9 and medical home access 10 or underinsurance 11 for children with special health care needs. Particular attention has been paid to differences seen in urban versus rural locales; the Agency for Healthcare Research and Quality (AHRQ) National Healthcare Disparities Report considers residents of rural areas to be a “priority population.” 12 They are more likely than urban residents to be in fair or poor physical health, 13 and less likely to have seen a health care provider or to have received preventive services.…”
mentioning
confidence: 99%
“…On the basis of previous findings (3,22), we used covariates related to socioeconomic and demographic status and potentially related to high BMI that are used in NHANES, the 2010 Census, and the American Community Survey (ACS). The variables considered were sex, race/ethnicity, age in months, education level of the household representative (level 1, <9th grade; 2, 9th–11th grade; 3, high school graduation or equivalent; 4, some college; 5, college graduate or above), household size (2 to ≥7 people), and family income or family poverty level (using the thresholds from ACS tables).…”
Section: Methodsmentioning
confidence: 99%
“…Because overweight or obese children are at a higher risk than normal-weight children for health problems, they are a target for intervention (2). There is evidence of disparities in pediatric obesity; Bethell et al (3) studied differences in obesity rates by race/ethnicity, insurance, and income and found within- and across-state disparities. Each of these factors can vary significantly across a city or county, so identifying small geographic areas with children at greatest risk for high body mass index (BMI) can be helpful in delivering cost-effective interventions.…”
Section: Introductionmentioning
confidence: 99%
“…The National Survey for Children’s Health (NSCH) includes a large enough sample size for state-specific estimates and has shown substantial variation across states in the prevalence and disparities in overweight and obesity among 10- to 17-year-old children. 5 NSCH, however, is based on parent-reported data, as opposed to measured data as can be found in NHANES. Parent-reported data are not recommended for estimating overweight prevalence in elementary school–aged children 6 because parents tend to overestimate height and underestimate weight.…”
mentioning
confidence: 99%